Vojaško soočanje supersil v Arktiki - Ferfila, Bogomil (Fakulteta za sociologijo, politične vede in novinarstvo v Ljubljani, 2015)
The author deals with military and ecological issues concerning the Arctic. This region is of strategic significance for both superpowers, especially as a polygon for developing strategic armament systems. Relations between Arctic states are given special attention, focused on unresolved issues (confrontations) concerning boarders. The militarisation process of the Arctichas also touched the interests of local communities and ecological groups. The Arctic is transforming into an ecological bomb due to nuclear activities such as nuclear experimenting, nuclear waste disposal, submarine accidents, etc., which have become almost everyday occurences. In conclusion, the author calls for the revitalisation and demilitarisation of the Arctic circle. Avtor obravnava vojaška in ekološka vprašanja, ki zadevajo Arktiko. To področje je strateškega pomena za obe supersili, zlasti kot poligon za razvijanje strateških oboroževalnih sistemov. Avtor posebej analizira odnose med aktičnimi državami in še posebej opozarja na nerešene spore glede meja. Proces militarizacije Arktike je prizadel tudi interese lokalnih skupnosti in ekoloških skupin. Arktika se spreminja v ekološko bombo, saj so radioaktivne dejavnosti: jedrski poskusi, odlaganje odpadkov, nesreče podmornic ipd. postale že vsakdanjost. Avtor v zaključku poziva k sanaciji in demilitarizaciji Arktike.